Pemahaman Mahasiswa PAI terhadap Konsep Ihsan dalam Kehidupan Bermasyarakat di IAINU Tuban - Abdul Khamid Nasimul Askhia; Sukron Ma’mun Andika; Siti Nurjannah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research aims to analyze in depth the level of understanding among Islamic Religious Education (PAI) students at the Islamic Institute of Nahdlatul Ulama (IAINU) Tuban regarding the concept of Ihsan and its implementation in community life. The urgency of this study is based on the strategic role of PAI students as future educators who are required to integrate spiritual dimensions and social ethics into their personalities. This research employs a quantitative approach with a descriptive survey method. Data were collected through a Likert scale questionnaire instrument that had been tested for validity and reliability, distributed to a sample of students selected through proportional random sampling. Data analysis was carried out systematically using descriptive statistics to calculate the mean value and categorization percentage across cognitive, affective, and applicative dimensions. The results indicated that the overall level of understanding of Ihsan among PAI students at IAINU Tuban falls into the low category, with a total mean score of 1.909. In detail, the affective dimension recorded the lowest score, indicating a weakness in the internalisation of spiritual consciousness, while the applicative dimension showed a slightly higher score but remained within the low category. It is concluded that there is a significant gap between the idealism of the Ihsan concept and the actual understanding of students in the field. These findings provide important implications for the need to reconstruct character-building strategies and the PAI curriculum, emphasizing the aspect of inner spiritual internalisation over mere formalistic cognitive knowledge transfer to produce graduates with authentic social piety.